2021
DOI: 10.29121/granthaalayah.v8.i12.2020.2872
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice on Junk Food Consumption Among Higher Level Students at Selected Educational Institutions of Kathmandu, Nepal

Abstract: Background: Junk food is a term for food that is of little nutritional value and often high in fat, sugar, salt, and calories. Junk food can have a detrimental effect on levels of energy and mental well-being. Consumption of large quantities of junk food is associated with a drastic reduction in the consumption of nutritious foods such as milk, fruits and vegetables. High revenues, rapid urbanization, free home delivery, mouthwatering commercials and foreign cuisines have led to growing trend in the consumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 13 publications
0
30
0
1
Order By: Relevance
“…A similar study found that 91.5 percent of the respondents consumed junk food at school and the least of the respondents consumed it at home (Sapkota & Neupane, 2017). In the same way, Subedi et al (2021) found that 7.9 percent of the respondents frequently consumed junk food at home, 38.4 percent of the respondents frequently consumed at college, 10.9 percent of the respondents frequently consumed at friend's house, 40.1 percent of the respondents consumed at street food stalls and the least (2.7%) percent of the respondents frequently consumed junk food at a restaurant. These studies show that most of the students use junk food at different places, junk food is popular among college students and it is found everywhere like groceries, hotel, restaurants, street shop, school and college canteens, etc.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…A similar study found that 91.5 percent of the respondents consumed junk food at school and the least of the respondents consumed it at home (Sapkota & Neupane, 2017). In the same way, Subedi et al (2021) found that 7.9 percent of the respondents frequently consumed junk food at home, 38.4 percent of the respondents frequently consumed at college, 10.9 percent of the respondents frequently consumed at friend's house, 40.1 percent of the respondents consumed at street food stalls and the least (2.7%) percent of the respondents frequently consumed junk food at a restaurant. These studies show that most of the students use junk food at different places, junk food is popular among college students and it is found everywhere like groceries, hotel, restaurants, street shop, school and college canteens, etc.…”
Section: Discussionmentioning
confidence: 73%
“…The results of present study show that38.4percent of the respondents indicated that the use of junk food was due to ready-made food, 29.1 percent respondents indicated that it saves time, 10.2 percent respondents indicated that it is easy to take, 13.6 percent respondents indicated that it is tasty, 4.5 percent respondents stated peer pressure as a cause and the least (4.2 percent) indicated effect of advertisement. A similar study found that 14.2 percent of the respondents consumed junk food to save time, 8.7 percent respondents consumed junk food due to changing lifestyle, 22.6 percent of the respondents consumed because of curiosity about new taste, 24.3 percent of the respondents consumed due to influence of advertisement and 30.2 percent of the respondents consumed due to its easy availability (Subedi et al, 2021). Another study showed that 72 percent of the respondents consumed junk food because of its delicious taste.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…(Nation, 2020) predicts that there will be a loss of learning after the covid-19 pandemic. This prediction was proved correct (Subedi et al, 2020), who researched the impact of the learning and teaching process in Nepal, and found that many problems occurred when the learning and teaching process was carried out online that the learning and teaching process was considered less effective. The same thing also happened in Indonesia, the research conducted by (Prawanti & Sumarni, 2020) regarding the assessment of online learning and its impact on students, parents, and also teachers, while the results of this study says that online learning in schools experiences many problems, so learning becomes less effective.…”
Section: Introductionmentioning
confidence: 86%
“…Literatürde, öğrencilerin eöğrenmeye yönelik tutumlarının olumlu olmasının; e-öğrenmeyi kullanma eğilimlerini etkilediği (Haznedar ve Baran, 2012), eğitimin kalitesini artırdığı (Biçer ve Korucu, 2020), öğrencinin başarısını yükselterek kalıcı bir öğrenme sağladığı (Yıldırım, Yıldırım, Çelik ve Karaman, 2014) belirtilmektedir. Ayrıca, pandemi sürecinde e-öğrenmenin, öğrenciler açısından; öğretim elemanı ile iletişimde zorluk yaşama (Diab ve Elgahsh, 2020), sosyalleşmede (Gherheș, Stoian, Fărcașiu ve Stanici, 2021;Thapa, Bhandari ve Pathak, 2021), motivasyon ve dikkatte olumsuz etkilenme (Bdair, 2021), teknik ve internet bağlantısı problemleri yaşama (Subedi, Nayaju, Subedi, Shah ve Shah, 2020;Thapa vd., 2021), duyuşsal ve psikomotor davranışlar kazanamama (Gherheş vd., 2021) gibi sınırlılıkları olduğu belirtilmektedir. Bunun yanı sıra, e-öğrenmenin bireysel, öğrenci merkezli ve etkileşimli bir öğrenme ortamı sağlaması (Biçer ve Korucu, 2020;Diab ve Elgahsh, 2020), ucuz ve kolay olması (Abdullaev ve Hidoyatova, 2020;Diab ve Elgahsh, 2020;Thapa vd., 2021;Yılmaz, Sezer ve Yurdugül, 2019), zaman ve mekân konusunda esneklik sağlaması (Biçer ve Korucu, 2020;Can, Özdemir ve Türksoy Işım, 2020;Park vd., 2022;Thapa vd., 2021;Yılmaz vd., 2019) gibi olumlu çıktıları da bulunmaktadır.…”
unclassified